Code-Switching in Social Media Identity and Social Meaning Among Indonesian Youth - Nasila Celsia; Syifa Daffa Ariestya; Annisa Nabila Faiza Zahra; Kushardiyanti Novinda (SM Institute, 2026)
This study examines code-switching practices among Indonesian youth on social media and their relation to identity construction and social meaning. Using a qualitative descriptive design, the study analyzed 25 code-switched utterances collected from public posts, captions, and comments on X, Instagram, and TikTok. The participants were Indonesian social media users aged 18 to 24 years. The data were classified into three types of code-switching, namely intra-sentential switching, inter-sentential switching, and tag-switching. The findings show that intra-sentential switching was the most dominant type, representing 44% of the data, followed by inter-sentential switching at 36% and tag-switching at 20%. English words and expressions were frequently inserted into Indonesian utterances to express emotion, modernity, confidence, and digital identity. Indonesian, meanwhile, was used to maintain intimacy, cultural closeness, and local belonging. The study concludes that code-switching among Indonesian youth is not random language mixing, but a meaningful sociolinguistic practice that reflects emotional expression, solidarity, social positioning, and hybrid identity in contemporary digital communication.